2002
DOI: 10.1123/ijsnem.12.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Blood Flow and Mitochondrial Function: Influence of Aging

Abstract: Skeletal muscle mitochondrial capacity (mito), tissue blood flow (BF) capacity, and oxygen exchange capacity (e.g., DO2) appear to be well matched. The different skeletal muscle fiber types and muscle remodeled, due to inactivity (e.g., related to aging or disease) or exercise training, exhibit widely differing aerobic capacities (VO2max). Yet, there are remarkably coordinated alterations in these 3 parameters in each of these conditions. With such a balance, there is likely shared control among these paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…30 Mitochondrial dysfunction is also linked to decreased muscle blood flow with aging. 39 Because eNOS reportedly modulates mitochondrial biogenesis, 26 eNOS upregulation may contribute to enhanced mitochondrial contents in muscles of E-DNIB mice. Furthermore, endurance exercise, which is considered to confer life-spanextending effects, enhances the expression of a mitochondrial sirtuin, SIRT3, in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…30 Mitochondrial dysfunction is also linked to decreased muscle blood flow with aging. 39 Because eNOS reportedly modulates mitochondrial biogenesis, 26 eNOS upregulation may contribute to enhanced mitochondrial contents in muscles of E-DNIB mice. Furthermore, endurance exercise, which is considered to confer life-spanextending effects, enhances the expression of a mitochondrial sirtuin, SIRT3, in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A review of muscle blood flow and aerobic capacity in healthy older people has demonstrated that the increase in muscle capillarization after endurance training would enhance oxygen and nutrient exchanges within the tissue by providing a larger surface area and shorter diffusion distance. 17 To the best of our knowledge, there has been no study that has examined calf muscle capillarization in adaptation to supervised treadmill-walking training in patients with IC. In the present study, we aimed to evaluate the effect of 12 weeks of supervised treadmill-walking training on muscle capillarization and the relationship between the changes in walking capacity and muscle capillarization in subjects with IC.…”
mentioning
confidence: 99%
“…It has been suggested previously [10] that alterations in skeletal muscle mitochondrial capacity, blood flow capacity and oxygen extraction capacity, all of which contribute to changes in maximal oxygen uptake associated with either physical inactivity (aging related) or exercise training. Moreover, the coordinated interplay between these parameters may play a role in limiting muscle oxygen uptake [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the coordinated interplay between these parameters may play a role in limiting muscle oxygen uptake [10] . This may explain the lack of differences between the groups with regard to oxygen extraction ca- pacity.…”
Section: Discussionmentioning
confidence: 99%